THE ROLE OF PERCEIVED HEALTH BENEFIT, BRAND IMAGE, AND DESIGN APPEAL TOWARDS HEALTH MASK REPURCHASE INTENTIONS AFTER EASING POLICY OF HEALTH PROTOCOL - Achmadi, Caesar Rosyad; Makarim, Muhammad Harfiansyah; Muzammil, Oktafalia Marisa (JURNAL ILMU MANAJEMEN, 2024)
This research entitled "The Influence of Perceived Health Benefit, Brand Image, and Design Appeal Towards Repurchase Intentions After Easing Policy of Health Protocol" has three objectives, namely: (1) Knowing the influence of perceived health benefit towards health mask repurchase intentions, (2) Knowing the influence of brand image towards health mask repurchase intentions, (3) Knowing the influence of design appeal towards health mask repurchase intentions. WHO (2020) describes a health mask as a loose, disposable device that creates a physical barrier between the wearer's mouth and nose as well as potential contaminants in the immediate environment. The method of this study is quantitative method. The population in this study was citizen of Indonesia in Java Island at least 17 years old who purchase health mask in recent three months. The sample in this study is 248 respondents. Data collecting method using online questionnaire and processed using SPSS version 26. The result of this study are: (1) Perceived health benefit has a significant effect on repurchase intention, (2) Brand image has a significant effect on repurchase intention, (3) Design appeal has a significant effect on repurchase intention.